Contamination Métallique D’une Espèce De Poisson (Brama Brama) De La Côte Dakaroise - Dione, Cheikh Tidiane; Diagne, Ibrahima; Ndiaye, Momar; Diebakate, Cheikhna; Ndiaye, Birame; Diop, Abdoulaye (European Scientific Journal, ESJ, 2018)
Pollution of metal origin constitutes one of the major risks in the world today. The metal elements can be very dangerous to human health when they are present in the environment at high concentrations. Thus, the evaluation of the metal contamination in marine organisms, especially fish, makes it possible to predict a possible contamination of humans. This paper focuses on studying the metal contamination of the beach of Soumbédioune, located at the western frontage of the area of Dakar. This site, where fish products are offloaded, is the home to Canal IV (West Canal), which drains urban wastewater. In this study, we evaluated the concentrations of the metal elements (Fe, Zn 2+ , Cr 6+) in the bodies of Brama brama using a visible spectrophotometry UV. The results obtained show a strong concentration of chromium plates of 24,5 µg/g which is obtained at the level of the liver. Zinc presents a content of 16,7 µg/g at the level of the skin, but it was not detected at the level of the liver and the flesh. The maximum iron content was recorded at the level of the liver with a value of 77,5 µg/g. However, the values obtained were definitely higher than the standards established by FAO and the CEE.